A Review on effect of SVM in Intrusion Detection System - Pushpam, C. Amali; Jayanthi, J. Gnana (International Journal of Computer Sciences and Engineering, 2018)
Intrusion detection system is a system combining both software and hardware that monitors and analysis huge volume of network traffic and detects malicious activities. The role of IDS in system security is significant but not sufficient. Data analysis is a part of the IDS process. Data mining is a data analytic tool. If it is integrated with IDS, performance of IDS will be elevated. One of the data mining classification algorithms is SVM. It is widely applied in IDS. In this paper a methodical study on SVM in IDS was done. This paper reports the effect of SVM in IDS. It is observed that SVM increases the performance of IDS and also it has some limitations. This review provides new ways for further research to overcome these limitations.